Simultaneous experimental comparison of low-GWP refrigerants as drop-in replacements to R245fa for Organic Rankine cycle application: R1234ze(Z), R1233zd(E), and R1336mzz(E). (15th April 2019) - Yang, Jingye; Ye, Zhenhong; Yu, Binbin; Ouyang, Hongsheng; Chen, Jiangping
Abstract: Micro-scale organic Rankine cycle (ORC) enables to convert low-temperature waste heat into electricity, which is presented as one of combined heat and power (CHP) technologies. The commonly utilized working fluid R245fa will be phased out in the near future because of significant impact to the climate change. In that case, new HFOs (hydrofluoroolefins) refrigerants are suggested as potential alternatives to R245fa because of extremely low GWPs (Global Warming Potential) and zero ODP (Ozone Depletion Potential). This paper experimentally analyzed the applicability of three HFO refrigerants as drop-in replacements to R245fa for micro-scale ORC application including R1234ze(Z), R1233zd(E) and R1336mzz(E). Control options were assigned to the refrigerant mass flow rate and the expander rotational speed. System performance indicators including cycle thermal efficiency and net power output were compared. Besides, the expansion behavior along with the heat transfer performance and pump work were also analyzed. For the whole range of operating conditions, comparing the maximum cycle thermal efficiency, R245fa is 4.6% while R1233zd(E), R1234ze(Z) and R1336mzz(E) are 4.7%, 4.5% and 3.1%, respectively; Comparing the maximum net power output, R245fa generates 11.4% more than R1233zd(E) and 3.1% than R1234ze(Z). Limited range of pressure ratio contributes to the extremely low electricity of R1336mzz(E). Highlights: Simultaneous experimental investigation of four refrigerants was implemented. R1234ze(Z) and R1233zd(E) were proved to be appropriate alternatives to R245fa. Small operating pressure ratio contributes to the lower efficiency of R1336mzz(E).